THE DIFFERENT MAGNETIC RESULTS OF ANEMI AND PPM MEASUREMENTS ON THE BURIED REMAINS OF A 13TH CENTURY FORTRESS - Muhammad Yanis; Marwan Marwan; Bukhari Bukhari; Nazli Ismail (Jurnal Natural, 2016)
This study aimed to evaluate the different magnetic results of an electromagnetic induction with proton magnetometer measurements on an archaeological site. The electromagnetic induction allows measuring both the apparent magnetic susceptibility in part per thousand (ppt) and the apparent electrical conductivity in millisiemens (mS/m). A proton magnetometer measures the total magnetic intensity in nanotesla (nT), caused by the induced and remanent magnetisations. An archaeological site where historical documents indicated the presence of a 13th century fortress that built by Lamuri Sultanate was selected as a test area. The measurement were conducted by divided the study area into 10 profiles.Some standard data processing have been applied to the measured data. The result of the first survey with electromagnetic induction showed low magnetic anomalies in the buried remains of Lamuri fortress. The similar value are shown as well by low magnetic field intensity in magnetometer measurement.